Integration of Natural and Artificial Laboratories to Strengthen Language Competence Based on Current Learning Issues - A'izzi, Rosda Aisyatul; Muhasona, Ihda Ulvi Ulia; Sa'adah , Ikfina Himmatus; Bakar, M. Yunus Abu (Jaanur Elbarik Indonesia, 2025)
This study aims to examine the integration of natural and artificial laboratories as a strategy for strengthening language competencies in accordance with the demands of modern learning. Through library research and content analysis methods, the study reviewed literature on the characteristics and models of integration of the two laboratories. The results of the study indicate that in the context of Arabic language learning in Islamic boarding schools, natural laboratories play a role in providing contextual learning experiences through authentic environments such as dormitories, mosques, and students' daily activities, while artificial laboratories provide structured learning through technology-based simulations. Although its implementation still faces limitations in facilities and educator competence, this approach has strong potential to be developed as an Arabic language learning strategy that is relevant to the demands of today's learning in Islamic boarding schools.